1997
DOI: 10.1111/j.1365-2133.1997.tb02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthralin (dithranol) in vitro inhibits human monocytes to secrete IL-6, IL-8 and TNF-α, but not IL-1

Abstract: Anthralin is a most widely used compound for topical treatment of psoriasis. Whereas numerous studies have ascertained anthralin as a safe and effective drug its mode of action still remains unclear. Previous studies demonstrated dose-dependent inhibition of a number of pro-inflammatory functions in human neutrophils and monocytes (MO). The aim of the present study was to investigate in stimulated MO the effect of anthralin on the secretion of cytokines which are of known importance for the psoriatic tissue re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 35 publications
1
13
0
3
Order By: Relevance
“…Anthralin inhibits human monocytes in vitro , 8 resulting in decreased levels of IL‐6, IL‐8, and TNF‐α but not IL‐1. The effects of dithranol on neutrophil superoxide generation in psoriatics have also been studied 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthralin inhibits human monocytes in vitro , 8 resulting in decreased levels of IL‐6, IL‐8, and TNF‐α but not IL‐1. The effects of dithranol on neutrophil superoxide generation in psoriatics have also been studied 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Reports on the effect of topical corticosteroids on dithranol irritation are largely contradictory 83,85,86 . Some studies indicate that the addition of a topical corticosteroid reduces dithranol irritation, 8 while others are contradictory 86 . A 24‐hour pretreatment and 3‐day post‐treatment with clobetasol‐17‐propionate did not influence dithranol‐induced inflammation after a 2‐hour application of 10% dithranol in petrolatum 87 .…”
Section: Miscellaneous Dermatosesmentioning
confidence: 99%
“…Numerous studies with conflicting results have attempted to investigate the mode of action of anthralin. Anthralin exerts antiproliferative (4) and anti‐inflammatory effects in psoriasis (5–7). It also activates NF‐κB, a central transcription factor of inflammatory and differentiation immune responses (NF‐κB) in keratinocytes (8) and induces an inflammatory reaction in normal skin (9).…”
Section: Introductionmentioning
confidence: 99%
“…An immunosuppressive effect of anthralin has also been proposed (10). Mrowietz et al (15) showed that anthralin inhibits the secretion of interleukin-6 (IL-6), IL-8, and tumor necrosis factor a (TNF-a) from lipopolysaccharide (LPS)-stimulated human monocytes. Our result that anthralin is more effective on onycholysis and subunguial hyperkeratosis reflects the possibility that this drug may act mainly on the nail bed and hyponychium.…”
Section: Discussionmentioning
confidence: 99%